Twitter Sebagai Sarana Mengakses Informasi Pelecehan Seksual (Studi Netnografi Thread Korban Pelecehan “Fetish Kain Bungkus”) - Rachel Anastasya; Dedi Sahputra; Ressi Dwiana (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2022)
This research entitled Social Media Twitter as a Means to Access Information of Sexual Harassment (Netnography Study of Harassment Victim’s Thread "Fetish Kain Bungkus"). This research aims to determine the activities and motives of using Twitter as a means of accessing the information about sexual harassment "Fetish Kain Bungkus". In this research, four students became informants then the researcher chose @collegemenfess, which is the auto base account as one of the accounts for finding informants. The method used is descriptive qualitative with the Netnography approach, by collecting data through observation and interviews. The results showed that the activity of using Twitter for accessing the information on cases of harassment "fetish kain bungkus", such as replies of negative and positive comments, threads created by victims, Twitter users who created threads of victim confession threads, and artist responses from their personal Twitter account against the case. Then the activities of all informants in accessing sexual harassment information are reading threads, share the thread with the like, retweet, and copy link the thread to be shared via other social media. Motives of Twitter users for accessing sexual harassment information based on the uses and gratifications theory were information motives, personal identity motives, integration and social interaction motives, and entertainment motives.